Aspek-aspek Ketuhanan dalam Teologis dan Pluralitas: Aspects of Divinity in Theology and Plurality - Saparuddin, Saparuddin (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
The study of this article is the aspects of God in theological and plurality of beings by raising three sub-problems, namely: 1) theological views about God (nature, justice, power, and the absolute will of God; 2) the concept of plurality in terms of various aspects; and 3) analysis of the plurality of beings and the unity of Khalik in Islamic perspective. This type of research is a text study using content analysis techniques. The results showed that Mu'tazilah views that God as not having nature and human actions is the will of man himself as a manifestation of God's justice, because humans have freedom. While Ash'ariyah views that God has nature and human actions are manifestations of God's will. The plurality of beings is a necessity as well as sunnatullah. The rejection of the plurality of beings is the rejection of something that is supposed to happen and the disbelief of God's destiny. Plurality is not only an awareness of a diverse society, consisting of various tribes and religions, which only illustrates the impression of fragmentation. But the recognition of plurality must be accompanied by a deep awareness to jointly build a relationship based on appreciation for diversity. Muslims, as the majority of the nation quantitatively, must set an example in realizing unity, unity and peace in the midst of the plurality and diversity of this nation by referring to the Prophet himself.